Robot innovation brings to agriculture efficiency, safety, labor savings and accuracy by plowing, milking, harvesting, crop tending/picking and monitoring. Issue 6 (14th October 2014) - Bloss, Richard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to review the dramatic entry of robotics into the field of agriculture. Design/methodology/approach – Research of efforts around the world to apply robots to agricultural needs and participation in webcasts of the latest in agricultural robotic development projects. Findings – Robots are enabling many new and innovative methodologies for performing traditional agricultural tasks of all types. Providing saving in labor, improved performance and faster field coverage. Practical implications – Readers may be very surprised at the many tasks that robots are already addressing in the agricultural field around the world and the way just applications can have major benefits to farming. Originality/value – A review of the wide range of the innovative application of robots to agricultural tasks worldwide.